Five new species of Ptychoptera Meigen with a key to species from China (Diptera: Ptychopteridae) - Kang, Zehui; Yao, Gang; Yang, Ding (Zootaxa, 2013)
Five new species of genus Ptychopter Meigen are described from China: Ptychoptera bannaensis sp. nov., P. lii sp. nov., P. lushuiensis sp. nov., P. qinggouensis sp. nov. and P. wangae sp. nov. A key to the known species of Ptychoptera in China is presented.